The Nexus amid Government Spending and Foreign Exchange Reserves in Nigeria - Adekunle, Ahmed (Acta Universitatis Danubius. Œconomica, 2024)
Nigeria and many other primary product-based export economies struggle from having enough foreign exchange reserves because it helps them meet their international financial obligations, which include paying for goods and services overseas and maintaining the value of their currency. Sequel to this, this study evaluates the nexus amid government spending and foreign exchange reserves in Nigeria. The study employed VECM to analysis the data obtained from Central Bank of Nigeria and World Development Indicators, 2021 covering 1986-2021. The findings of the study revealed there is cointegration between foreign exchange reserves and other employed independent variables. The coefficient of government spending has a detrimental impact on FORES, as was indicated. Accordingly, a 0.26% decrease in FORES will result from a percentage increase in government spending. The study recommends that efforts should be made to expand revenue-generating strategies while also reducing spending. The current administration should be urged to prioritize and carry out measures that will broaden the tax base, particularly to include economic agents in the informal sector who may be eligible and contribute to increasing tax revenue, in light of the issues raised by the ongoing negative budget balance. encouragement of growth and development driven by the private sector.